Education is the future of the nation - Əhmədova Sevinc İslam q. (Academics and Science Reviews Materials, 2023)
The development of society in the era of globalization has affected both education and all areas. Education has a strong impact as a human value. Mankind has come to such a decision that as a result of education, ordinaryness and ignorance among people can be eliminated. To this end, education is of great importance in the world at present. Also in our republic, in connection with all this, as the demand for education and specialists obtained as a result of training has grown, there is a need to modernize education and prepare a specialist who meets all the requirements as a result of modernization. . For this reason, the content, essence, quality and purpose of education in the Republic of Azerbaijan began to be updated.Today, education attracts attention as a strategic sphere in the Republic of Azerbaijan. Thus, great attention is paid to the improvement of the education system in Azerbaijan. In modern times, the penetration of modernization into the education system, like other areas, has created conditions for achieving development. Modernization of education occupies an important place at a certain stage of our development. As a democratic and legal state, the Republic of Azerbaijan takes as its basis the integration of its educational system into the educational system of developed countries. But what is the reason for this? Because the main goal in the modernization of education is the formation of a comprehensively developed personality. Today, the implementation of the modernization of education, i.e. modernization, is one of the new directions of enriching its essence. What is the quality of education? As in all areas of social activity, the quality for a student in education is the presence of high standards, this is a different, exceptional feature, this is high thinking. [1, s. 184].